The interrelationships and continuing relevance of biodiversity conservation, systematics and biological collections in the Philippine context (2010)
Studies of biological diversity, the science of systematics and the management of biological collections may be regarded as independent disciplines but are definitely interrelated and inseparable. Their interrelationships are discussed briefly and broadly, although some details are included, mainly those that are not usually brought up by other advocates of these three fields as they are affected by various socio-politico-economic realities under Philippine society. Hopelessness is another reality to contend with in terms of these three biological fields. In contrast, perseverance by time-tested Filipino scientists who are/were experts in this field provide inspiration and important lessons to present to future generations of systematists, biodiversity specialists, conservationists and curators. Some of those scientists are mentioned herein to provide concrete examples. Biodiversity, systematics and biological collections will continue to be relevant to our existence as a people and to any society, no matter how poor it..